967 Scrubbing Up: A Drain on Sustainability - Yoganathan, S; Zabkiewicz, C; Jones, T; Shingles, L (British journal of surgery, 2023)
Aim Surgical scrub is a vital step in infection control prior to operating. Hospitals typically opt for a traditional tap or a sensor-operated tap to control their water source. This project compared the water usage and efficiency per surgical scrub for the two different taps. Method Theatre system was reviewed to determine total number of staff members who scrubbed in for each operation, over a one-month period within one health board. Average scrubbing time and quantity of water used per scrub was calculated by observing multiple different staff members. Results During September 2022, 6076 staff members scrubbed in for theatres. The average time spent handwashing was 2 minutes and 26 seconds, however only 47 seconds worth of running water was used to wash their hands. Sites using traditional taps used approximately 18.6L of water whilst sensor-operated taps used 13.2L per surgical scrub. This equated to 110,752 litres of water used over the month solely for scrubbing up. Sensor-operated taps would run for 63 seconds when activated with the modal number of times sensors were activated 3. Therefore, traditional taps were more efficient with 32% of running water used for surgical scrub compared to 25% for sensor-operated taps. Conclusions Sensor-operated taps used less water per surgical scrub; however, the operating time of the taps reduced its efficiency. Coordinating scrubbing up and ‘sharing’ one tap or adjusting the sensor taps operating time are simple step to minimise water wastage. Furthermore, the use of ‘waterless scrub’ solution is a viable option whilst also minimising infection risk.